Profil Kemampuan Berpikir Kritis Siswa SMA Berdasarkan Cornell Critical Thinking Test Level X - Maulana Pratama, Shovian; Suyana, Iyon; Gina Nugraha, Muhamad; Praginda, Wandy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking is one of the essential competencies required in the twenty-first century to prepare students to address global challenges and solve complex real-world problems. However, the results of the 2022 Programme for International Student Assessment (PISA) indicate that Indonesian students' science achievement remains below the OECD average, highlighting the need to examine students' critical thinking profiles as a basis for developing effective instructional strategies. This study aimed to describe the critical thinking profile of senior high school students based on the Cornell Critical Thinking Test (CCTT) Level X. A quantitative descriptive research design was employed involving 98 tenth-grade students from a public senior high school in Bandung, Indonesia. Data were collected using the Cornell Critical Thinking Test Level X, consisting of 76 multiple-choice items assessing four indicators: induction, observation and credibility, deduction, and assumptions. The data were analyzed using descriptive statistics. The results revealed that the overall mean score of students' critical thinking was 36.7, which falls within the moderate category. Regarding the individual indicators, induction was predominantly classified as moderate (37%), observation and credibility as moderate (46%), deduction as moderate (39%), while assumptions was predominantly classified as low (32%). These findings indicate that students' critical thinking skills have not yet developed optimally, particularly in the assumptions indicator. Therefore, instructional practices should systematically engage students in activities that foster induction, observation and credibility, deduction, and assumptions to promote the more effective development of critical thinking skills.